Trends in PICU Admission and Survival Rates in Children in Australia and New Zealand Following Cardiac Arrest - Straney, L.; Schlapbach, L.; Yong, G.; Bray, J.; Millar, J.; Slater, A.; Alexander, J.; Finn, Judith (2015)
OBJECTIVES: To describe the temporal trends in rates of PICU admissions and mortality for out-of-hospital cardiac arrests and in-hospital cardiac arrests admitted to PICU over the last decade. DESIGN: Multicenter, retrospective analysis of prospectively collected binational data of the Australian and New Zealand Paediatric Intensive Care Registry. All nine specialist PICUs in Australia and New Zealand were included. PATIENTS: All children admitted between 2003 and 2012 to PICU who were less than 16 years old at the time of admission. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: There were a total of 71,425 PICU admissions between 2003 and 2012. Overall, cardiac arrest accounted for 1.86% of all admissions (1,329 cases), including 677 cases of in-hospital cardiac arrest (51.0%) and 652 cases of out-of-hospital cardiac arrest (49.0%). Over the last decade, there has been a 29.6% increase in the odds of PICU survival for all pediatric admissions (odds ratio, 1.30; 95% CI, 1.09-1.54). By contrast, there was no significant improvement in the risk-adjusted odds of survival for out-of-hospital cardiac arrest admissions (odds ratio, 1.03; 95% CI, 0.50-2.10; p = 0.94) or in-hospital cardiac arrest admissions (odds ratio, 1.03; 95% CI, 0.54-1.98; p = 0.92). CONCLUSIONS: Despite improvements in overall outcomes in children admitted to Australian and New Zealand PICUs, survival of children admitted with out-of-hospital cardiac arrest or in-hospital cardiac arrest did not change significantly over the past decade.